Prognosis of immune checkpoint inhibitors-induced myocarditis: a case series - Isabelle Serre; Olivier Lambotte; Stephane Ederhy; Jean-Marie Michot; Jean-Luc Faillie; Alexandre Thibault Jacques Maria; Xavier Quantin; Candice Lesage; Patricia Rullier; Philippe Guilpain; Romaric Larcher; Kada Klouche; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Background Immune checkpoint inhibitors (ICI) have transformed cancer treatment over the last decade. Alongside this therapeutic improvement, a new variety of side effects has emerged, called immune-related adverse events (irAEs), potentially affecting any organ. Among these irAEs, myocarditis is rare but life-threatening.Methods We conducted a multicenter cross-sectional retrospective study with the aim of better characterizing ICI-related myocarditis. Myocarditis diagnosis was based on the recent consensus statement of the International Cardio-Oncology Society.Results Twenty-nine patients were identified, from six different referral centers. Most patients (55%) were treated using anti-programmed-death 1, rather than ICI combination (35%) or anti-programmed-death-ligand 1 (10%). Transthoracic echocardiography was abnormal in 52% of them, and cardiac magnetic resonance showed abnormal features in 14/24 patients (58%). Eleven patients (38%) were classified as severe. Compared with other patients, they had more frequently pre-existing systemic autoimmune disease (45% vs 6%, p=0.018), higher troponin level on admission (42-fold the upper limit vs 3.55-fold, p=0.001), and exhibited anti-acetylcholine receptor autoantibodies (p=0.001). Seven patients (24%) had myocarditis-related death, and eight more patients died from cancer progression during follow-up. Twenty-eight patients received glucocorticoids, 10 underwent plasma exchanges, 8 received intravenous immunoglobulins, and 5 other immunosuppressants. ICI rechallenge was performed in six patients, with only one myocarditis relapse.Discussion The management of ICI-related myocarditis may be challenging and requires a multidisciplinary approach. Prognostic features are herein described and may help to allow ICI rechallenge for some patients with smoldering presentation, after an accurate evaluation of benefit–risk balance.